Integrated transcriptomic and metabolomic analyses elucidate the regulatory role of SlBEL11 in tomato fruit ripening - Dong, Xiufen; Lu, Jie; Guo, Yun; Zhang, Qihan; Yang, Qin; Peng, Jingyi; Tian, Li (Frontiers in Plant Science, 2025)
Transcription factors serve as key regulators in orchestrating fruit ripening, modulating gene expression networks that govern physiological processes such as color change, texture softening, and sugar accumulation in response to hormonal signals like ethylene and abscisic acid. SlBEL11, a BEL1-like transcription factor, was previously shown to mediate premature fruit abscission in tomato. However, the molecular mechanisms by which SlBEL11 regulates ripening, including its direct target genes, metabolic pathways, and interaction networks, remain largely unknown. In this study, an integrated approach combining untargeted metabolomics and transcriptomics was employed to investigate the metabolic and molecular alterations in wild-type (WT) and SlBEL11-RNAi knockdown tomato fruits. UPLC-MS/MS analysis identified a total of 189 differentially expressed metabolites (DEMs), with 74 upregulated and 115 downregulated in SlBEL11-RNAi compared to the WT. Meanwhile, transcriptome analysis uncovered 665 differentially expressed genes (DEGs), including key regulators directly associated with ripening processes. Conjoint analysis demonstrated significant enrichment of both DEGs and DEMs in critical metabolic pathways, such as ascorbate and aldarate metabolism, glycolysis, and phenylpropanoid biosynthesis. These pathways were demonstrated to be directly or indirectly modulated by SlBEL11, highlighting its central role in coordinating metabolic reprogramming during fruit maturation. Specifically, SlBEL11 appears to fine-tune the balance among energy supply, cell wall modification, and antioxidant biosynthesis, thereby influencing fruit texture, nutritional quality, and shelf-life. Collectively, these findings not only provide novel insights into the regulatory network of SlBEL11 in tomato ripening but also offer potential genetic targets for the development of tomato cultivars with improved postharvest traits and enhanced fruit quality and secondary metabolite production.